Population Pharmacokinetic Study of Vancomycin in Chinese Pediatric Patients with Hematological Malignancies. Issue 12 (18th November 2020) - Wang, Huijuan; Huang, Lingfei; Wang, Junyan; Ni, Yinghua; Zhu, Zhengyi; Gao, Peng; Hu, Yan; Zhang, Liwen; Yang, Jufei; Fang, Luo
Abstract : Study Objectives : Vancomycin is a primary antibiotic for the treatment of severe infections in children with malignant hematological disease. However, precise dosing of vancomycin is difficult in children because of high interindividual variability and limited data of pharmacokinetic profiles. The present study aims to develop a population pharmacokinetic (PPK) model for vancomycin in Chinese pediatric patients with hematological malignancies. Design : This was a retrospective pharmacokinetic study. Setting : The setting for this study was a tertiary‐care children's hospital. Patients : This study included 92 pediatric patients with hematological malignancies who received vancomycin and experienced therapeutic drug monitoring from February 2017 to December 2018. Measurements and Main Results : A PPK model was generated with a nonlinear mixed effects model. In addition, required doses to achieve target therapeutic concentrations were simulated based on the final model. A one‐compartment model with first‐order elimination fit the concentration data best. Actual body weight (BW) and glomerular filtration rate (GFR) were the significant influential factors on the clearance (CL) of vancomycin. The final PPK model for CL was CL (L/h) = 4.18  × GFR / 145 0.741 × BW / 25 K, K =  BW ‐ 0.856 / BW ‐ 0.856 + 6 . 53 ‐ 0.856, and the volume of distribution was 22.3 L. The model proved to be robust and reliable. Reference dosing regimens were proposed based on the final model. Conclusions : A PPK model of vancomycin was established for Chinese pediatric patients with hematological malignancies using a nonlinear mixed effects model, which provided a reference for the clinical application of vancomycin.